In search of Alzheimer’s disease treatment methods: trends of clinical trials - G. Pakulaitė; V. Regelskytė; E. Audronytė; J. Kuzmickienė; G. Kaubrys (Neurologijos seminarai)
There is a strong necessity to develop new treatments for Alzheimer’s disease (AD) as its frequency is rapidly growing with the ageing population. There were 25 pharmacological agents involved in phase I trials, 52 in phase II, and 28 agents in phase III clinical trials in 2017. More than two thirds (70%) of these agents are developed as disease-modifying therapies. Their mechanisms of action are targeted mainly to amyloid and tau related pathology. Almost one third (27%) of the agents comprise the group of symptomatic treatment. There is a number of factors that determine the current failure of the research. The factors include incomplete understanding of AD pathophysiology, limited agent access to the central nervous system, and lack of diagnostic and predictive biomarkers. Although AD treatment studies have given no clear positive results in recent decades, research is actively continued due to the growing economic and social burden of the disease.